Analisis Penegakan Hukum Pidana Bagi Pelaku Pencemaran Lingkungan Hidup: Undang-Undang Nomor 32 Tahun 2009 Tentang Pengelolaan dan Perlindungan Lingkungan Hidup - Erva Yunita; Ratu Wida Widyaningsih Suhandi; Suryani Alawiyah; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The issues that are the subject of discussion are what elements constitute a criminal offense in environmental pollution violations and what sanctions are applied to perpetrators of environmental pollution crimes. The type of research is normative research with an analytical approach to legislation Number 32 of 2009 concerning Environmental Management and Protection. The data collection used is literature study and reviewing literature that is relevant to the research problem. The results of the research are that the elements of criminal acts consist of acts of pollution, environmental damage, non-compliance with regulations, environmental disorder, pollution which causes significant negative impacts. Threat of Sanctions Violations of formal offenses include administrative sanctions in the form of warnings, administrative fines, or revocation of business permits. If it is considered a criminal violation, it will be subject to criminal sanctions or a fine. Threat of Sanctions for Material Offense Violations, namely criminal sanctions in the form of large fines or imprisonment depending on the level of environmental damage and the impact it causes.